ANALISIS PENATAAN RUANG KAWASAN LINDUNG KABUPATEN PANDEGLANG DENGAN APLIKASI GIS DAN REMOTE SENSING - Rika S. Santoso; Rinekso Soekmadi; Lilik Budi Prasetyo (Media Konservasi, 2011)
The need for space is increasing along with the growth of population. It had become one of the matters which caused exploitation of natural resources and abuse of space uses. Protected area provided life support system, but in fact it had been degraded and experienced function changes.  Pandeglang as one of areas with high natural resources potential had also encountered environmental problems.  Geographic information system (GIS) could provide the latest data and help in to reach decision of space policy to push the protection area management. The research was carried out on September until November 2009 with the purpose to: (1) identify the legal formal protected area based on the Presidential Decree Number 32 year 1990 about protected area management; (2) identify the gap of legal formal and actual protected areas, and the abuse of protected areas spatial pattern, and; (3) formulate strategy and policy direction in supporting the management of legal formal protected areas.  The data was collected through thematic maps, remote sensing and direct observation.  Data analysis was based on the results of overlay analysis and the percentage of deviation (summary) analysis. The result showed that the actual protected areas, based on the distribution of forest function (DFH), in Pandeglang Regency were Ujung Kulon National Park (TNUK), Carita Nature Recreation Park (TWA) and protected forest, while the actual protected areas based on spatial area allocation in spatial area arrangement plan (RTRW) in Pandeglang Regency were TNUK and protected forest.  The gap between the legal formal protected area with the actual protected area was 99,957.20 Ha (35.55%). All protected areas were dominated by forest in different coverage.  There were inconsistency of planning steps and spatial pattern abuse of protected areas.  Management of the legal formal protected areas could be supported through the assignment of an institution with authority/mandate and responsibility in the management of legal formal protected areas, particularly toward natural disaster prone areas and local protected areas.  The RTRW document should be reviewed to provide actual data, the use of similar format of data reference, and reach a consistent spatial arrangement.   Keywords: legal formal, actual, protected areas, gap, GIS, Pandeglang.